Improving Schoolyard Wind Environments: Case Studies in Two Schools in Nanjing - Liu, Anqi; Xu, Qiuxia; Gao, Jiahao; Xu, Zhen; Han, Lingyun (Geographica Pannonica, 2019)
Wind environment as an essential aspect of urban micro-climate is usually studied as an important factor affecting human wind comfort and thermal comfort in public open space. Less studied is how wind environments influence schoolyard serving for children and teenagers who are more sensitive to air temperature and air pollution. This paper presents a study using XFlow for wind speed evaluation based on CFD (Computational Fluid Dynamics) simulation, and Ecotect Analysis for thermal comfort evaluation. Choosing Nanjing Mochou Lake Primary School and Nanjing NO.13 Middle School Suojin Campus as case studies, it offers an evaluation of wind environments in these two schoolyards and surrounding open spaces. Simulation shows that improvements should be made to build better wind environments around both schools. Scenarios are developed subsequently by adjusting buildings in study areas at the scale of blocks and school buildings, proving the efficiency of improvements for a more comfortable wind environments. This study focuses on schoolyard wind environments from the standpoint of children and teenagers, suggesting that research on urban micro-climate can be expanded in multiple directions so that as many social groups in different ages as possible benefits, i.e. have healthier urban life.